will give brainliest
Which expression is equivalent to 17x − 8x + 2 and why?


2 − 9x, because (17x − 8x) + 2 = −9x + 2 = 2 − 9x

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

11x, because 17x − 8x + 2 = 9x + 2 = 11x

7x, because 17x − 8x + 2 = 17x − 10x = 7x

Respuesta :

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Step-by-step explanation:

The given expresion is 17x-8x+2.

We want to find an expression that is equivalent to this expression.

We first simplify:

[tex]17x - 8x + 2[/tex]

This implies that

[tex]9x + 2[/tex]

By the commutative property;

[tex]9x + 2 = 2 + 9x[/tex]

The second choice is correct.

Answer:

2 + 9x, because (17x − 8x) + 2 = 9x + 2 = 2 + 9x

Step-by-step explanation: